Exploring the role of DeepSeek artificial intelligence in patient education and diagnosis for chronic kidney disease: promise and precautions - Pathuri, Sriram (International Journal of Research in Medical Sciences, 2025)
The integration of artificial intelligence (AI) into healthcare is revolutionizing how patients access medical information.